2019
DOI: 10.1155/2019/5240898
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Coenzyme Q Protects Sepsis-Induced Acute Lung Injury by Activating PI3K/Akt/GSK-3β/mTOR Pathway in Rats

Abstract: The aim of our study was to assess the effects of mitochondrial coenzyme Q (MitoQ) on sepsis-induced acute lung injury (ALI) and investigate its possible mechanisms. The cecal ligation and puncture (CLP) method was used to establish a septic ALI model. Rats were randomly divided into Con group, CLP group, MitoQ group, and MitoQ + LY294002 group. The survival rate of the rats was recorded, and the survival rate curve was plotted. Moreover, the ratio of wet/dry weight (W/D) in lung tissue was measured. The activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 34 publications
(39 reference statements)
1
36
0
Order By: Relevance
“…Thus, mitoQ exerts protective effect on I/R-induced intestinal barrier dysfunction [ 40 ]. Recently Ruirui Li and his colleague revealed that mitoQ protected lung function and inhibited cell apoptosis in lung tissue by activating the PI3K/Akt/GSK-3 beta/mTOR pathway [ 41 ]. Our findings indicate that mitoQ plays an efficient role in LPS induced acute lung injury via inhibiting mitochondrial ROS (mtROS) production in both in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mitoQ exerts protective effect on I/R-induced intestinal barrier dysfunction [ 40 ]. Recently Ruirui Li and his colleague revealed that mitoQ protected lung function and inhibited cell apoptosis in lung tissue by activating the PI3K/Akt/GSK-3 beta/mTOR pathway [ 41 ]. Our findings indicate that mitoQ plays an efficient role in LPS induced acute lung injury via inhibiting mitochondrial ROS (mtROS) production in both in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The rat sepsis model was established using the cecal ligation and puncture (CLP) method, as previously described ( 17 ). Briefly, all rats were deprived of from food 12 h before surgery, but had free access to water during this time.…”
Section: Methodsmentioning
confidence: 99%
“…But (Rademann et al 2017) (Lowes et al 2008) (Supinski et al 2009) (Zang et al 2012) (Lowes et al 2013) (Wu et al 2015) ) (Prauchner 2017) (Fock et al 2018) (Li, Ren, et al 2019) But (Rademann et al 2017) (Elsakka et al 2007) (Paludo et al 2013) (Majolo et al 2015) (continued) (Zhao et al 2004) (Adlam et al 2005) (Cho J et al 2007) (Neuzil et al 2007) (Bakeeva et al 2008) (Skulachev et al 2009 (Keller et al 1998) (Murakami et al 1998) (Fujimura et al 1999) (Kim et al 2002)…”
Section: Pathologymentioning
confidence: 99%